LGBTTQ Movements in Turkey: The People Living in “Other Side” - Sarı, Özgür (European Journal of Multidisciplinary Studies, 2017)
As well as all around the World, in Turkey, non-heterosexual (lesbian, bisexual, gay, transsexual, transgender, quir) oriented movements and identities are much more visible in public sphere. For LGBTTQ people, to be more visible in the public sphere, to manipulate policies and public opinion, to give voice for their freedom and rights, NGOs and initiatives based on sexual orientation out of hegemonic sexual identity have been improving rapidly in the World. Parallel to the global rise, in Turkey LGBTTQ movements and NGOs are more and more active today as a new social movement. In the parameters behind the development of LGBTTQ movements, totally eight LGBTTQ NGOs are active in Turkey’s cities Istanbul, Ankara, ?zmir, Eski?ehir and Diyarbak?r. To transform the heterosexist, patriarchal and militarist public sphere in Turkey, the LGBTTQ NGOs prepare some activities, demonstrations and the most famous one “Istanbul Pride”. In this study, their propaganda techniques, media tools, projects to effect public opinion, and their relations to other NGOs and initiatives are seen as typically the items of new social movements. Behind the rise of sexual oriented social movements, the decline of national identities, the dissolution of citizenship, class identities and the decline of identities based on production relations play crucial roles.